Review of records of sawfishes (Chondrichthyes: Pristidae) from Fiji, with deletion of Pristis zijsron Bleeker, 1851 and Pristis sp. from the fauna - Duffy, Clinton; Seeto, Johnson; Trnski, Tom (Zootaxa, 2011)
Sawfishes (Pristidae) are large shark-like batoids with a distinctive flattened, greatly elongated rostrum armed on each side with a row of large transverse teeth. Two genera and at least four species occur in the Indo-West Pacific, of which Anoxypristis cuspidata (Latham, 1794), Pristis microdon Latham, 1794 and P. zijsron Bleeker, 1851 have widespread distributions and P. clavata Garman, 1906 appears to be restricted to northern Australia (Compagno & Last, 1999; Last & Stevens, 2009; Phillips et al., 2011). All sawfishes are threatened by over fishing and habitat loss, with range reductions and local extinctions reported for several species (Simpfendorfer, 2000; Monte-Luna et al., 2007; Last & Stevens, 2009; Wueringer, et al. 2009; Phillips et al., 2011). All Indo-Pacific sawfishes are assessed by the IUCN as Critically Endangered with decreasing population trends (IUCN Red List of Threatened Species, http://www.iucnredlist.org/, 10 Sep. 2011).